2022
DOI: 10.1021/jacs.2c01588
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming Efficiency Limitation of Cluster Light-Emitting Diodes with Asymmetrically Functionalized Biphosphine Cu4I4 Cubes

Abstract: Electroluminescent (EL) nanoclusters holding promise for newgeneration cluster light-emitting devices (CLEDs) rapidly emerge. However, slow radiation and serious quenching of cluster emitters largely limit the device performance. Herein, we report two monofunctionalized biphosphine chelated Cu 4 I 4 clusters [DMACDBFDP] 2 Cu 4 I 4 and [DPACDBFDP] 2 Cu 4 I 4 . The asymmetric modification and electron-donating effect of acridine groups lead to the iodine-toligand charge transfer predominant excited states of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 46 publications
1
41
0
Order By: Relevance
“…The device structure is shown in Figure 9 b. In 2022, Hui Xu et al reported two bisphosphine-chelated asymmetric Cu 4 I 4 NCs, [DMACDBFDP] 2 Cu 4 I 4 and [DPACDBFDP] 2 Cu 4 I 4 , to overcome the efficiency limit of the Cu 4 I 4 NC-based LEDs [ 87 ]. The asymmetric modification of the acridine group and the electron-donating effect led to the NCs exhibiting an excited state dominated by iodine-ligand charge transfer, resulting in a significant increase in the singlet radiation rate constant and a decrease in the triplet non-radiative rate constant.…”
Section: Electroluminescent Light-emitting Diodes With Metal Nanoclus...mentioning
confidence: 99%
“…The device structure is shown in Figure 9 b. In 2022, Hui Xu et al reported two bisphosphine-chelated asymmetric Cu 4 I 4 NCs, [DMACDBFDP] 2 Cu 4 I 4 and [DPACDBFDP] 2 Cu 4 I 4 , to overcome the efficiency limit of the Cu 4 I 4 NC-based LEDs [ 87 ]. The asymmetric modification of the acridine group and the electron-donating effect led to the NCs exhibiting an excited state dominated by iodine-ligand charge transfer, resulting in a significant increase in the singlet radiation rate constant and a decrease in the triplet non-radiative rate constant.…”
Section: Electroluminescent Light-emitting Diodes With Metal Nanoclus...mentioning
confidence: 99%
“…In addition, CPLE nanoscale architectures, including metal clusters, 30,31,37,41−43 because of the lack of knowledge of the emission 47,48 and CPLE mechanisms. 49 Here, we designedly synthesized an enantiomeric pair of bidentate S-based ligands (R/S)-binaphthyldithiophosphoric acid 50 (abbreviated as R/S-PS) with axial chirality to obtain fully S-protected enantiopure metal clusters. The nested homosilver R/S-[S 2− @Ag 12 @S 8 @Ag 32 (PS) 24 ] 2+ (R/S-Ag 12 Ag 32 ) cluster (Figure 1) crystallizes in the P432 space group, in which the chiral Ag 32 (PS) 24 shell has a C 4 rotation axis, while the inter S 2− @Ag 12 @S 8 moieties display achiral characteristics because of the presence of inversion (Figure 2).…”
Section: ■ Introductionmentioning
confidence: 99%
“…In addition, CPLE nanoscale architectures, including metal clusters, ,,, nanoparticles, and quantum dots, are some of the most dynamic architectures in nanoscience. Efficient strategies for modulating CPLE metal clusters are rare because of the lack of knowledge of the emission , and CPLE mechanisms …”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] TADF can achieve a nearly 100% internal quantum efficiency (IQE) without using metal atoms through the reverse intersystem crossing (rISC) process owing to the small splitting energy (DE ST ) between the lowest triplet excited state (T 1 ) and the lowest singlet excited state (S 1 ). [7][8][9][10][11][12][13][14][15][16][17] To achieve a small DE ST , conventional TADF emitters generally need a near-vertical twist angle between the electron acceptor (A) and electron donor (D). The twisted structure gives the highest occupied molecular orbital (HOMO) and the lowest unoccupied molecular orbital (LUMO) a large degree of separation, thus resulting in a small electron exchange energy.…”
Section: Introductionmentioning
confidence: 99%